Cyberknife Radiosurgery for the Treatment of Head and Neck Cancer: A Systematic Review - Soman, Cristalle; Alghamdi, Shahad Ramzi Mohammed; Alazemi, Faisal Nahar M.; Alghamdi, Abdulaziz Ahmad Abdullah (European Journal of Dentistry, 2021)
Cyberknife radiosurgery is a frameless stereotactic robotic radiosurgery which has shown to deliver better treatment outcomes in the treatment of advanced head and neck (H&N) carcinomas, especially in previously irradiated and recurrent cases. The aim of the study was to perform a systematic review of the available data on the outcomes of Cyberknife radiosurgery for treatment of head and neck cancer and to evaluate its collective outcomes. This systematic review was registered with the university with the registration no. FRP/2019/63 and was approved by the Institutional Review Board (RC/IRB/2019/132). Literature search was performed in the following: PubMed, Science direct, SciELO, MyScienceWork, Microsoft Academ EMBASE, Directory of Open Access Journals, and Cochrane databases with the keywords “Cyberknife,” “oral cancer,” “oropharyngeal cancer,” and “head and neck cancer” and data was extracted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The records identified were 147 manuscripts. Excluded articles included 5 duplicate articles, 33 abstracts, 101 full text articles due to being off-topic, case reports, review, non-English, 1 survey, and 2 other articles containing data extracted from a main study which was already included. A total of 5 articles were evaluated for qualitative synthesis. The mean dose of Cyberknife radiosurgery delivered for previously irradiated recurrent H&N carcinoma patients was 34.57 Gy, with a mean sample size of 5 studied during the period of 2000 to 2016. The available evidence from the systematic review indicates that Cyberknife can be an efficacious treatment option for recurrent previously irradiated H&N carcinoma, especially for nonresectable tumors. There is paucity of homogenous data and studies in this arena; hence, meta-analysis could not be performed. Further standardized studies are essential, especially where the treatment of H&N carcinoma is considered.
Keywords: cyberknife radiosurgery; oropharyngeal neoplasms; treatment outcomes of cyberknife; cyberknife radiotherapy; head and neck neoplasm; targeted radiation therapy; stereotactic radiotherapy; robotic radiosurgery